A coalition formation game framework for peer-to-peer energy trading. (1st March 2020) - Tushar, Wayes; Saha, Tapan Kumar; Yuen, Chau; Azim, M. Imran; Morstyn, Thomas; Poor, H. Vincent; Niyato, Dustin; Bean, Richard
Highlights: The paper studies peer-to-peer trading based on social cooperation. A coalition formation game is designed to model the trading between prosumers. It is shown that the coalitions are stable and optimal. Motivational psychology is exploited to study the outcome of the scheme. It is shown that outcomes are prosumer-centric. Abstract: This paper studies a social cooperation backed peer-to-peer energy trading technique by which prosumers can decide how they can use their batteries opportunistically for participating in the peer-to-peer trading. The objective is to achieve a solution in which the ultimate beneficiaries are the prosumers, i.e., a prosumer-centric solution. To do so, a coalition formation game is designed, which enables a prosumer to compare its benefit of participating in the peer-to-peer trading with and without using its battery and thus, allows the prosumer to form suitable social coalition groups with other similar prosumers in the network for conducting peer-to-peer trading. The properties of the formed coalitions are studied, and it is shown that (1) the coalition structure that stems from the social cooperation between participating prosumers at each time slot is both stable and optimal, and (2) the outcomes of the proposed peer-to-peer trading scheme are prosumer-centric. Case studies are conducted based on real household energy usage and solar generation data to highlight how the proposed scheme can benefit prosumers through exhibiting prosumer-centric properties.